2019
DOI: 10.4252/wjsc.v11.i9.565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental stressors on stem cells

Abstract: Environmental toxicants are ubiquitous, and many are known to cause harmful health effects. However, much of what we know or think we know concerning the targets and long-term effects of exposure to environmental stressors is sadly lacking. Toxicant exposure may have health effects that are currently mischaracterized or at least mechanistically incompletely understood. While much of the recent excitement about stem cells (SCs) focuses on their potential as therapeutic agents, they also offer a valuable resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The pathways mediating the stemness of NSCs, such as Notch, WNT/β-catenin, and Hedgehog signaling, are also critical in glioma stem-like cells to drive tumorigenicity[ 14 , 15 ]. Recently, novel therapeutic approaches are established with the goal of not only reducing the tumor burden but also targeting CSCs involved[ 16 ].…”
Section: Cscsmentioning
confidence: 99%
“…The pathways mediating the stemness of NSCs, such as Notch, WNT/β-catenin, and Hedgehog signaling, are also critical in glioma stem-like cells to drive tumorigenicity[ 14 , 15 ]. Recently, novel therapeutic approaches are established with the goal of not only reducing the tumor burden but also targeting CSCs involved[ 16 ].…”
Section: Cscsmentioning
confidence: 99%
“…1998 ). Genetic or epigenetic alterations in hESCs induced by environmental stressors, if they occur in vivo , may affect the fate and development of the embryo and the health status of the individual later in life ( Worley and Parker 2019 ). MeHg exposures have been associated with a higher number of abnormal blastocysts ( Kajiwara and Inouye 1986 ) and blastocyst degeneration ( Spindle and Matsumoto 1987 ) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these lineages then further differentiates into cells of different organs and systems; examples of this differentiation include the endoderm forming gut epithelial cells, pancreas, and hepatocytes; the ectoderm forming neural epithelium, embryonic ganglia, and stratified squamous epithelium; and the mesoderm forming cartilage, bone, and smooth and striated muscles (Li et al 2015;Thomson et al 1998). Genetic or epigenetic alterations in hESCs induced by environmental stressors, if they occur in vivo, may affect the fate and development of the embryo and the health status of the individual later in life (Worley and Parker 2019). MeHg exposures have been associated with a higher number of abnormal blastocysts (Kajiwara and Inouye 1986) and blastocyst degeneration (Spindle and Matsumoto 1987) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollutants can significantly impact hematopoiesis [ 17 , 18 ]. We previously reported that heavy metals in the living environment such as cadmium, lead, and Hg significantly influenced the function of HSCs and the committed progenitors, leading to aberrant myelopoiesis and/or lymphopoiesis [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%